Peripheral Organ Injury After Stroke - Wang, Jin; Zhang, Jiehua; Ye, Yingze; Xu, Qingxue; Li, Yina; Feng, Shi; Xiong, Xiaoxing; Jian, Zhihong; Gu, Lijuan (Frontiers in Immunology, 2022)
Stroke is a disease with high incidence, mortality and disability rates. It is also the main cause of adult disability in developed countries. Stroke is often caused by small emboli on the inner wall of the blood vessels supplying the brain, which can lead to arterial embolism, and can also be caused by cerebrovascular or thrombotic bleeding. With the exception of recombinant tissue plasminogen activator (rt-PA), which is a thrombolytic drug used to recanalize the occluded artery, most treatments have been demonstrated to be ineffective. Stroke can also induce peripheral organ damage. Most stroke patients have different degrees of injury to one or more organs, including the lung, heart, kidney, spleen, gastrointestinal tract and so on. In the acute phase of stroke, severe inflammation occurs in the brain, but there is strong immunosuppression in the peripheral organs, which greatly increases the risk of peripheral organ infection and aggravates organ damage. Nonneurological complications of stroke can affect treatment and prognosis, may cause serious short-term and long-term consequences and are associated with prolonged hospitalization and increased mortality. Many of these complications are preventable, and their adverse effects can be effectively mitigated by early detection and appropriate treatment with various medical measures. This article reviews the pathophysiological mechanism, clinical manifestations and treatment of peripheral organ injury after stroke.